Extraction of feijoa (Acca Sellowiana Berg) fiber and its application in thick sausage meat products - Ochoa Palma, Marcia Idilma; Moreno Avilés, Karen Elizabeth; Valencia Caicedo, Yarixa Nadia (Ingeniería Química y Desarrollo, 2022)
This project aims to develop a thick pasta sausage with the addition of feijoa food fiber, for this you must know the properties of it. An experimental methodology is applied where several formulations and sensory analysis are performed, through which the degree of acceptance of the sausage is determined, thus defining the final formulation. The standard recipe with its respective process is also established, in addition a bromatological and microbiological examination is performed, to guarantee the safety of the product. This research shows that feijoa fiber is a variable product, because it integrates perfectly with meat products, in the process of making sausages, providing them with nutritional properties, highlighting their aroma, flavor and texture.
Keywords: addition; elaboration; sausage; feijoa; fiber